PENINGKATAN KEMAMPUAN MEMBACA NASKAH DRAMA ANAK MELALUI METODE PEMODELAN - Nanda Saputra (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This study aims to determine the improvement of children's drama script reading ability using the modeling method. The approach used in this study is a qualitative approach with the type of Classroom Action Research (CAR). Data were taken from test results, observations, and interview results. The data source was 38 of 4th grade students of MIN 41 Pidie. The results showed an increase in the number of students who had completed the learning from 39% in the pre-action test or before the learning took place. Then it increased to 76% in the first cycle, and increased again to 89% in the second cycle. The use of the modeling method can also increase the activity of teachers and the 4th grade students at MIN 41 Pidie when learning to read children's drama scripts. This is evidenced by the increase in the percentage of teacher activity in the first cycle, which is 81% to 91% in the second cycle. Student activity in the first cycle is 83% to 93% in the second cycle. It can be concluded that the modeling method can improve students' ability to read children's drama scripts.